2014
DOI: 10.1093/comnet/cnu020
|View full text |Cite
|
Sign up to set email alerts
|

Percolation and cascade dynamics of spatial networks with partial dependency

Abstract: Recently, it has been shown that the removal of a random fraction of nodes from a system of interdependent spatial networks can lead to cascading failures which amplify the original damage and destroy the entire system, often via abrupt first-order transitions. For these distinctive phenomena to emerge, the interdependence between networks need not be total. We consider here a system of partially interdependent spatial networks (modelled as lattices) with a fraction q of the nodes interdependent and the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…As the system approaches criticality, the green nodes (dead ends) far outnumber the white nodes (backbone) [5,6]. than r in each direction, in line with the models used in [19][20][21], figure 1(a). This means that a node at location (i, j) in lattice A can depend on the continued functioning of a node in lattice B located at ′ ′ i j ( , )only if | − ′| ⩽ i i r and | − ′| ⩽ j j r. Of the + r (2 1) 2 nodes that fulfill this condition for any given node, one is chosen uniformly at random.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…As the system approaches criticality, the green nodes (dead ends) far outnumber the white nodes (backbone) [5,6]. than r in each direction, in line with the models used in [19][20][21], figure 1(a). This means that a node at location (i, j) in lattice A can depend on the continued functioning of a node in lattice B located at ′ ′ i j ( , )only if | − ′| ⩽ i i r and | − ′| ⩽ j j r. Of the + r (2 1) 2 nodes that fulfill this condition for any given node, one is chosen uniformly at random.…”
Section: Introductionsupporting
confidence: 58%
“…The phase transition is second-order for < r r c , and p c increases monotonically with r. For ⩾ ≈ r r 4 c , the transition is first order and p c decreases asymptotically towards its value for = ∞ r , see figures 2(a) and 3(a). In contrast, fully interdependent lattices with structural dependency undergo a first-order phase transition only when > ≈ r r 8 c [19,20]. In all cases, the p c of process-based dependency is substantially higher (more vulnerable) than structural dependency, due to the fact that the current-carrying backbone is always smaller than the GCC, see figure 3(a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…When it exists, the networks preserve their functionality, and when it does not exist, the networks split into fragments so small they cannot function on their own. The percolation processes on other network of networks topologies have been presented and discussed in [7,9,12,[14][15][16][17][18][19][20].…”
Section: Percolation and Diffusionmentioning
confidence: 99%
“…Studies on spatially embedded interdependent networks found that in many cases they are significantly more vulnerable then non-embedded systems [27]. Further studies deal with similar models but restrict the dependency links to be of limited length [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%